Konseling Religius Migran Indonesia di Belanda - Ahmad Muhammad Diponegoro; Mujidin Mujidin; Agungbudiprabowo Agungbudiprabowo (PSIKOPEDAGOGIA Jurnal Bimbingan dan Konseling, 2017)
This study aims to examine in depth of the effect of religious counseling towards the religious behavioral adaptation of Indonesian migrant in the Netherlands. The study used a case study of twelve Indonesian Muslim migrants in the Netherlands with male and female sex with a religious counselor taken with purposive sampling techniques. The data collection tool used in this study was by interview and in-depth observation. Data analysis techniques using a model of qualitative data analysis Miles Huberman with data reduction steps, display data and draw conclusions. The result of this study showed that the religious counseling played positive roles in the life of Indonesian Muslim migrants group in the Netherlands. Those roles include community life, relationship with Allah and relationship among Islam people. The findings of this study can be a strategy for the counselor in assisting Muslim migrants in a non-muslim country on the behavioral adaptation